Comparison and optimization of SAR‐PAGE tests for erythropoietins in doping analysis. Issue 1 (26th November 2019) - Zhou, Xinmiao; Zhang, Lisi; He, Sen; Shen, Li; He, Chunji
Abstract: Erythropoietins (EPOs) are substances listed in S2 of the World Anti‐Doping Agency (WADA) Prohibited List and are used commonly by athletes to increase endurance performance. According to the current WADA Technical Documents, sarcosyl‐polyacrylamide gel electrophoresis (SAR‐PAGE) followed by western blotting to differentiate erythropoietins based on their molecular weights is the only method that can be used for both screening and confirmation of all types of erythropoietins. The efficiency of immunopurification and protein transfer is crucial for ensuring the selectivity and sensitivity of erythropoietin detection. Several comparisons and optimization of the SAR‐PAGE tests were conducted in this study. We optimized the first blotting conditions and then compared different immunopurification methods based on their selectivity, repeatability, and sensitivity for both urine and blood analysis. Additionally, rapid procedures for both urine and blood analysis were established and compared. The two‐step procedure at 1.0 mA/cm 2 for 60 min followed by 1.56 mA/cm 2 for 20 min increased the blotting efficiency compared with the commonly used constant current approach. Comparison of immunopurification revealed no significant difference in selectivity and sensitivity between the different methods. For other factors, such as operation complexity, time and cost, a StemCell® purification kit followed by single blotting and magnetic beads followed by double blotting are recommended for urine screening and confirmation, respectively. While magnetic beads and a MAIIA® kit followed by double blotting are recommended for both screening and confirmation of blood samples, respectively. To ensure high sensitivity and selectivity, double blotting is recommended for a rapid procedure for both urine and blood analysis.